Male Involvement in Family Planning Utilization and Associated Factors in Womberma District, Northern Ethiopia: Community-Based Cross-Sectional Study - Wondim G; Degu G; Teka Y; Diress G (Dove Medical Press, 2020)
Getinet Wondim,1 Genet Degu,2 Yohannes Teka,2 Gedefaw Diress3 1Key Population and Partner Notification Service, CDC, Woldia, Ethiopia; 2Department of Midwifery, College of Medicine and Health Science, Debre Markos University, Debre Markos, Ethiopia; 3Department of Public Health, College of Health Science, Woldia University, Woldia, EthiopiaCorrespondence: Gedefaw Diress Tel +251913756945Email gedefawdiress@gmail.comBackground: Reproductive health issues are an inclusive concern for both men and women. In order to improve maternal health, strengthening male participation in family planning is an important public health initiative. Yet, men are still the main decision-makers in the family in Ethiopia, especially in the rural community. There is little concrete evidence of the extent of male participation in family planning and its barriers in rural settings.Purpose: To assess the magnitude of male involvement in family planning utilization and its associated factors in the rural community of northern Ethiopia.Materials and Methods: A community-based cross-sectional study design was carried out on 620 currently married men. A multi-stage sampling technique was used to select the participants of the study. Data were collected using interviewer-administered structured questionnaires. Multivariable logistic regression analysis was performed to identify variables associated with male participation in family planning.Results: In this study, only 12.5% of males were directly involved in the use of family planning using a male contraceptive method, and about 60.0% of males were involved in family planning through spousal communication and approval. Being educated [AOR=1.64; 95% CI: (1.12– 2.62)], having an educated partner [AOR= 1.77; 95% CI: (1.17– 2.94)], having a positive attitude towards family planning [AOR=2.27; 95% CI: (1.53– 3.36)], discussing with wife [AOR= 2.51; 95% CI: (1.69– 3.72)] and having adequate knowledge about family planning [AOR=1.92; 95% CI: (1.28– 2.87)] were positively associated with male involvement in family planning utilization whereas having more than three children [AOR=0.32; 95% CI: (0.15– 0.70)] was negatively associated with male involvement in family planning utilization.Conclusion: In general, as compared to the national recommendation, the level of male participation in family planning utilisation was low. In order to improve male participation in family planning, improving male knowledge and attitudes towards family planning is essential.Keywords: family planning, male involvement, contraceptive, Womberma